PLATELET-RICH PLASMA AND PLATELET FIBRIN: STANDARDIZED PREPARATION PROTOCOLS, MECHANISMS OF ACTIVATION, STORAGE STABILITY, AND REGULATORY FRAMEWORKS - Khyzhnyak, Mykhailo; Vasilyeva, Iryna; Potapov, Oleksandr; Tsyndrenko, Oleksandr; Gafiychuk, Yuri (Eastern Ukrainian Medical Journal, 2025)
Objective. To summarize current methods for obtaining platelet-rich plasma (PRP) and platelet-rich fibrin (PRF), their biological properties, activation protocols, and regulatory aspects of clinical application.Methods. A comprehensive analysis of recent literature on the preparation, standardization, and clinical use of platelet-derived biomaterials was performed. Special attention was given to two-step centrifugation protocols for producing pure platelet-rich plasma (P-PRP), low-speed centrifugation techniques for injectable PRF (i-PRF), and methods for constructing fibrin-based matrices (P-PRF).Results. Platelet-derived biomaterials represent a concentrated source of growth factors (PDGF, TGF-β, VEGF, IGF-1, EGF, FGF, HGF) that promote tissue regeneration, angiogenesis, and immunomodulatory effects. The efficacy of PRP/PRF depends on donor hematological parameters, centrifugation settings, activation strategies, and delivery methods. This review outlines optimal platelet concentration ranges, discusses the rationale for anticoagulant selection, and describes quality control methods as well as classification systems (PAW, DEPA, MARSPILL). Regulatory aspects of PRP application in Ukraine are also highlighted, including cases in which GMP certification is mandatory.Conclusion. PRP and PRF occupy a prominent position in regenerative medicine; however, the lack of standardized protocols and unified guidelines hampers the comparability of clinical outcomes. Future development in this field requires methodological harmonization, large-scale clinical studies, and the implementation of GMP standards in commercial production.